The Values Contained in the Developed Books of Islamic Education at the upper Three Grades in the Primary Stage in Saudi Arabia - Alatawi, Fahad Oudah; Qutb, Iman Mohammad Mabrouk (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the values that are contained in the developed books of Islamic education at the upper three grades in primary stage in Saudi Arabia. In order to achieve that, the study analyzed the content of textbooks of Islamic education as study sample and prepared for this purpose a study tool, which has a group of values that are classified into seven major categories: (faith, devotional, social and moral, mental and practical, the national, economic and Aesthetic). The study confirmed validity and stability of the tool. The study tool included an open question to specialists about the values which should be included in the textbooks of Islamic education in case of being inadequate. The study concluded the following results: The total occurrences of the contained values in the books of Islamic education were (1315) values, the devotional field frontrunner with the (485) duplicates, followed by the ideological field with (299) duplicates, followed by social and moral with (278) duplicates, followed by the aesthetic field with (92) duplicates, followed by mental and scientific domain with (48) duplicates, and finally the national field with (24) duplicates. The results of the study revealed a list of value categories that contained (10) values.